(untitled) (Eurasian Journal of Learning and Academic Teaching, 2024)
This article explores some kind of effective methods for increasing vocabulary in English. It emphasizes the significance of a robust vocabulary in language skills and offers practical tips for learning and remembering new words. The techniques include reading extensively, using flashcards and mnemonic devices, participating in discussions and writing exercises, as well as making use of online resources and vocabulary-building apps. By implementing these methods consistently, learners can boost their vocabulary skills and improve their overall English language abilities